Q and frequency tunable second order LC bandpass filter for Long Term Evolution (LTE) receiver - Thangasamy, Veeraiyah; Kamsani, Noor Ain; Hamidon, Mohd Nizar; Sulaiman, Nasri; Bukhori, Muhammad Faiz (Hoehere Bundeslehranstalt und Bundesamt fuer Wein- und Obstbau, 2014)
This paper presents a design of Q and center frequency tunable LC bandpass filter at 5.2GHz using 130nm CMOS technology. Centre frequency tuneability was achieved by implementing NMOS transistors biased as varactor. Q-factor enhancement and tuneability was achieved using the negative transconductance effect of the cross coupled differential pair. Simulation results achieved shows that the center frequency of the filter is tunable through 5.2GHz to 5.337GHz and the Q-factor of filter tunable through 100 to 577 under 1.2V supply. Furthermore, the achieved 1-dB compression point, IIP3 and noise figure are -2.3dBm, 8.5dBm and 10.65dB respectively.